Regulating complement in the kidney: insights from CFHR5 nephropathy - Gale, Daniel P. (The Company of Biologists Limited, 2011)
Complement factor H related protein 5 (CFHR5) nephropathy is a monogenic disorder of complement regulation that is endemic in Cyprus. The disease is characterised by haematuria, C3 glomerulonephritis and kidney failure. Its identification suggests a role for the CFHR5 protein in the regulation of complement in the kidney. In this review, we discuss how studying CFHR5 nephropathy can contribute to our understanding of the role of complement in kidney diseases such as dense deposit disease, C3 glomerulonephritis and atypical haemolytic uraemic syndrome.